Coins, bodies, games, and gold : the politics of meaning in archaic Greece - Kurke, Leslie (Princeton University Press, 1999)
The invention of coinage in ancient Greece provided an arena in which rival political groups struggled to imprint their views on the world. This book analyses the ideological functions of Greek coinage.